WAYS OF PROMOTING AND PROMOTING INTERNATIONAL MARATHON COMPETITIONS AMONG YOUTH IN UZBEKISTAN (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Currently, the level of development of the international marathon held in foreign countries has increased year by year. Six of the world's largest marathons are held every year, including Boston, Chicago, New York, Tokyo, Berlin and London, the Dubai Marathon in the UAE, and the Seoul Marathon. Marathons abroad bring good profits to the organizers. Nevertheless, organizing marathons is a promising business. They have a reliable prize pool - from $313,000 in London to $825,000 in New York. Each of the first place winners will receive 100,000 US dollars, but Uzbek track and field athletes will not participate in these competitions.